The Effect of Combined Application of Biological, Organic and Chemical Fertilizers on Growth Responses and Quality of Several Potato Cultivars (Solanum tuberosum) in Northern Khuzestan Province - mansour timar; Shahram Lack; Alireza Shokuhfar; Naser Zarifinia; mojtaba alavifazel (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
In order to investigate the effect of nutrition management of different potato cultivars, on the quantitative and qualitative traits and nutrients content in the potato tuber, an experiment was conducted in Safi Abad Agricultural Research Center of Dezful as split plot based on completely randomized block design with three replications during two cropping years 2016-2017. The studied treatments are nutrition at three levels (application of urea, triple superphosphate and potassium sulfate fertilizers (180, 150 and 100 kg.ha-1, respectively), nutrition with humic acid organic fertilizer and phosphorus Barvar-2 (1kg and 100 g.ha-1, respectively) and combined nutrition treatment with chemical fertilizers + humic acid+ phosphorus Barvar-2) in main plots and potato cultivars (Sante, Arinda and Savalan) in sub plots. The results showed that chemical fertilizer treatments had a higher percentage of dry matter than other nutritional treatments and nutritional treatment with chemical fertilizer+ humic acid+Barvar-2 was in the next rank. Also, findings showed that Sante cultivar in the second year with application of chemical fertilizer had higher percentage of dry matter than other treatments by 27.69 percent followed by Savalan cultivar was in the same nutrition treatment in the second year of cultivation 26.47 percent dry matter. Based on the results of mean comparison, the nitrogen content of potato in the second year increased significantly compared to the first year and the highest nitrogen content was observed in the studied treatments in the second year of the study. The highest amount of phosphorus was the humic acid+ Barvar-2 treatment in the second year by 3.31 mg. g-1 in Arinda cultivar. Generally, humic acid treatments were better than other nutritional treatments in terms of phosphorus levels. Also, according to the qualitative traits, the lowest levels of solanine toxin were obtained in the first and second year in Savalan cultivar, by 546.4 and 632. 2μg.g-1 dry matter respectively. In chemical fertilizer nutrition treatments, Arinda cultivar had the lowest amount of solanine toxin in both years of research. Overall, the results of this study showed that Savalan cultivar had better performance than other cultivars and in general, the application of phosphorus Barvar-2 and humic acid improved the quantitative and qualitative characteristics of potatoes in the northern Khuzestan climatic conditions.